Use of communication technologies by people with type 1 diabetes in the social networking era. A chance for improvement. Issue 2 (April 2016) - Giménez-Pérez, Gabriel; Recasens, Assumpta; Simó, Olga; Aguas, Teresa; Suárez, Ana; Vila, Maria; Castells, Ignasi
Highlights: Use of social networks for health purposes by patients with type 1 diabetes is low. Willingness to share information with the health team is high; mainly via e-mail. Willingness to participate in professional led social networks is substantial. A higher involvement of health teams may be needed to implement health Web 2.0. Being a single centre study, the results may not be applicable to other populations. Abstract: Aims: To evaluate the health-related use of Web 2.0 tools by patients with type 1 diabetes. Methods: Cross-sectional survey assessing views and usage of the Internet, Apps and Web 2.0. Results: Number of participants: 289 (age 42.8 ± 13.5 years; diabetes duration 18.4 ± 12.2 years; 58.7% males; 39% with an upper secondary or higher education level). Web 2.0 usage for health purposes was low with 19.6% and 14% of Web 2.0 members (147; 50.9%) having health–related contacts and posting health comments. Health-related Apps were used by 35.4% of Smartphone owners (161; 55.7%). 75.3% patients would share information online with professionals, preferably through e-mail (78.7%) rather than Facebook (47.7%). 141 (66.5%) of those willing to share information would participate in a professional-moderated Facebook group. Conclusions: Web 2.0 and Apps usage for health purposes is low. The difference between the use of Web 2.0 networks and the willingness to participate in professional-moderated Web 2.0 groups points to the need of a higher implication of health professionals in promoting Web 2.0 technologies if these are to be adopted in a clinical setting. Currently, e-mail is the tool to be considered when aiming to increase online communication with patients with type 1 diabetes.